Cultural Container. A successful case of divulgation and promotion of contemporary youth culture - Linares-Pedrero, Agustín; Lechuga-Jiménez, Clotilde (My University, 2021)
The Vice-Rectorate for Culture of the University of Malaga (UMA), decided in 2016 at the beginning of the academic course, to create the brand and site entitled “Contenedor Cultural” (Cultural Container). The main proposal was/is to attract the younger public (UMA’s students and citizens in general), through cultural activities focused on music, theater and film events, so as workshops and conferences related to those performances. For this, an annual weekly program is designed in which know-how is applied in two directions: one is to develop contracts in internships for students who have passed half of their Bachelor Degree credits (ECTS), and another is to capture and give visibility to young talent, favoring the local and incorporating a national scope from time to time. The contents are grouped into themes within monthly periodicity such as the month of Women in March; Spring topics in April; or Science Fiction and Fantasy in November. These topics can be renewed according to current demand news such as COVID-19 or the month dedicated to Multiculturalism. Social and cultural benefits strengthen the two directions previously mentioned. In the former, students acquire skills, challenges and abilities required at work positions related to cultural industries such as design and visual communication; dam communication and networks; event technicians (light, sound, production), etc. In the latter, musicians, actors, performance, writers, filmmakers, visual artists, etc., are promoted and / or their professional careers are reinforced. In addition, financial remuneration for their activity are considered. As a highly remarkable result, public who assist to Cultural Container are enriched with contemporary and very up-to-date level culture. .
EU_CUL. Exploring Cultural Heritage
Keywords: Arte contemporáneo; University community; Artistic community; Contemporary art; Cultural management; Dissemination